Radar Range Equation for Ultra Wideband Signals and Ultra Short Pulses - Avdeev, V.B. (Радиофизика и радиоастрономия, 2002)
The range equation for radiolocation of an object and its elements with ultrawideband signals (UWBS) and ultra short pulses (USP) are resulted. The criticism of other published equations is given.